Eco benign synthesis of silver nanoparticles using Matthiola incana's extract for heightened biomedical applications - Shahnaz, Shahnaz; Khan, Hidayat Ullah; Begum, Rafia; Fozia, Fozia; Durrani, Faran; Ahamd, Ijaz; Al-Rejaie, Salim S.; Milošević, Marija; Mohany, Mohamed (Biotechnology and bioprocess engineering, 2025)
This study focused on synthesizing silver nanoparticles (AgNPs) using a green approach by reducing silver nitrate via methanolic extract of Matthiola incana . The synthesized AgNPs were characterized by different analytical techniques, including FTIR, UV/Vis, scanning electron microscopy (SEM), X-ray diffraction (XRD), and energy dispersive X-ray (EDX) analysis. The UV/Vis spectrum of AgNPs exhibited the surface plasmon resonance (SPR) absorption at 411 nm, confirming the synthesis of AgNPs. The effective stabilization of AgNPs through bioreduction and capping may involve functional groups of biomolecules, as indicated by the FTIR spectroscopy. The EDX analysis demonstrates that AgNPs accounted for 51.92% of the total weight, and SEM confirmed the spherical morphology of AgNPs with a small particle size ranging from 40 to 100 nm. Furthermore, the M. incana -mediated AgNPs and crude extract exhibited potent antioxidant and antibacterial activities. The DPPH free radical scavenging assay was used to examined the antioxidant activity of crude extract which displayed a promising antioxidant effect with IC 50 value of 612.06 ± 0.25 µg/mL in contrast to AgNPs that showed IC 50 value of 507.2 ± 0.003 µg/mL. Moreover, the antibacterial activity of AgNPs showed more potent inhibitions that was 60 ± 0.003% against the bacterial strains of Staphylococcus aureus and the Escherichia coli strain revealed 41 ± 0.55% inhibitions, at the dose of 100 µg/mL, respectively. Thus, overall results demonstrate an effectiveness of M. incana -mediated AgNPs for combating Gram-positive ( S. aurus ) and Gram-negative ( E. coli ) bacteria and antioxidant activity to develop an active drug for different infectious diseases.